2016
DOI: 10.1590/01047760201622032197
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC GAIN FROM DIFFERENT SELECTION METHODS IN Eucalyptus macarthurii PROGENIES IN DIFFERENT ENVIRONMENTS

Abstract: ABSTRACT:The aims of this research was to estimate genetic parameters of Eucalyptus macarthurii progenies and to predict genetic gain for different selection methods. In order to evaluate the gains, eleven progenies tests were studied. These tests were installed in 1997, in randomized blocks design, in two sites, with 5 replicates of five plants per plot. The progenies were evaluated, from the first to the eighth year, regarding the variable diameter at breast height (DBH). The genetic parameters were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The capability of genetic material to perform well under a wide range of environmental conditions is an essential factor in improvement programs (MORAES et al, 2014;ENGEL et al, 2016;PUPIN et al, 2018). The term adaptability is used to designate the capacity of the genetic material to take advantage of environmental stimuli, and stability refers to the capacity of genotypes to be have predictably in the face of environmental stimuli (VENCOVSKY; BARRIGA, 1992;MORAIS et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The capability of genetic material to perform well under a wide range of environmental conditions is an essential factor in improvement programs (MORAES et al, 2014;ENGEL et al, 2016;PUPIN et al, 2018). The term adaptability is used to designate the capacity of the genetic material to take advantage of environmental stimuli, and stability refers to the capacity of genotypes to be have predictably in the face of environmental stimuli (VENCOVSKY; BARRIGA, 1992;MORAIS et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Six progenies showed stability and adaptability in the three study sites (Table 5), and were among the top 20 in all environments. These progenies may be recommended for orchards for the production of improved seeds in all three experimental sites, due to the simple-type G×E interaction, including the attributes stability and adaptability, as also reported in an work with Eucalyptus macarthurii H.Deane & Maiden (Engel et al, 2016).…”
Section: Resultsmentioning
confidence: 59%
“…Across the ages studied, a negligible difference was observed among the CV g , indicating that selection is possible at 3 and 5 years of age. Engel et al (2016), evaluating early selection in E. macarthurii, observed genetic correlations above 0.63 among the ages studied, but the correlations at younger ages were lower. Sato et al (2010) identified high and positive correlations between the ages of 4 and 21 years in C. maculata.…”
Section: Resultsmentioning
confidence: 85%